Domestic money and US output and inflation - Yunus Aksoy; Tomasz Piskorski (Goethe University Frankfurt, Center for Financial Studies (CFS), 2001)
Recent empirical research found that the strong short-term relationship between monetary aggregates and US real output and inflation, as outlined in the classical study by M. Friedman and Schwartz, mostly disappeared since the early 1980s. In the light of the B. Friedman and Kuttner (1992) information value approach, we reevaluate the vanishing relationship between US monetary aggregates and these macroeconomic fundamentals by taking into account the international currency feature of the US dollar. In practice, by using official US data for foreign flows constructed by Porter and Judson (1996) we find that domestic money (currency component of M1 corrected for the foreign holdings of dollars) contains valuable information about future movements of US real output and inflation. Statistical evidence here provided thus suggests that the Friedman and Schwartz's stylized facts can be reestablished once the focus of analysis is back on the domestic monetary aggregates.
urn:nbn:de:hebis:30-9858
Keywords: E3; E4; E5; 330; Foreign holdings; US monetary aggregates; Information value; Friedman-Schwartz's evidence